Chlorinated polyvinyl chloride composite material for vehicle lampshade and preparation method of chlorinated polyvinyl chloride composite material
By introducing maleic anhydride grafted chlorinated polyvinyl chloride, modified filler and other raw materials into chlorinated polyvinyl chloride, a chlorinated polyvinyl chloride composite material with good mechanical properties, corrosion resistance and high temperature resistance, the problem of insufficient impact resistance and thermal stability of chlorinated polyvinyl chloride during application is solved.
Patent Information
- Application Number
- CN202510036340.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-03-21
AI Technical Summary
When used, chlorinated polyvinyl chloride has problems such as poor impact resistance and poor thermal stability, and its performance needs to be improved.
By combining chlorinated polyvinyl chloride with maleic anhydride grafted chlorinated polyvinyl chloride, modification filler, aminopropylheptyl-cage polysilsesquioxane and ethylene-tetrafluoroethylene copolymer and other raw materials, a chlorinated polyvinyl chloride composite material with good mechanical properties, corrosion resistance and high temperature resistance is prepared.
It improves the impact resistance, corrosion resistance and high temperature resistance of chlorinated polyvinyl chloride composite materials, extends the service life, and the preparation method is convenient to operate and control, has high production efficiency, and is suitable for industrial production.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a chlorinated polyvinyl chloride composite material for a vehicle lamp cover and a preparation method thereof. Background Art
[0002] Chlorinated polyvinyl chloride (CPVC) is a product of polyvinyl chloride (PVC) that is further chlorinated and modified. In addition to having many excellent properties of polyvinyl chloride, CPVC has much better corrosion resistance, corrosion resistance, heat resistance, solubility, flame retardancy, and mechanical strength than PVC. It is widely used in construction, chemical industry, metallurgy, shipbuilding, electrical appliances, textiles and other fields. At present, with the development of economy and social progress, the automobile industry is booming, and CPVC also has a very broad application prospect in the production of automobile parts such as headlight covers. However, although the chemical stability, heat resistance and tensile properties of CPVC are better than those of PVC, due to the special molecular structure of CPVC, it still has problems such as poor impact resistance and poor thermal stability when used, and its performance needs to be improved. Summary of the invention
[0003] The purpose of the present invention is to solve the above-mentioned deficiencies in the prior art and provide a chlorinated polyvinyl chloride composite material for a vehicle lamp cover, wherein the chlorinated polyvinyl chloride composite material has good mechanical properties, corrosion resistance and high temperature resistance and a long service life.
[0004] Another object of the present invention is to provide a method for preparing a chlorinated polyvinyl chloride composite material for a vehicle lamp cover. The method is convenient to operate and control, has high production efficiency, is suitable for industrial production, and the prepared product has stable quality and reliable performance.
[0005] The objective of the present invention is achieved through the following technical scheme: A chlorinated polyvinyl chloride composite material for a vehicle lamp cover, comprising the following raw materials in parts by weight: 70-80 parts of chlorinated polyvinyl chloride, 10-15 parts of maleic anhydride grafted chlorinated polyvinyl chloride, 8-14 parts of a modified filler, 4-8 parts of a compatibilizer, 4-8 parts of a heat stabilizer, 4-9 parts of an ethylene-tetrafluoroethylene copolymer, 2-5 parts of a lubricant, 2-5 parts of aminopropylheptyl-cage polysilsesquioxane, and 2-6 parts of a processing aid.
[0006] The chlorinated polyvinyl chloride composite material for vehicle lampshade of the present invention is mainly made of chlorinated polyvinyl chloride, and maleic anhydride grafted chlorinated polyvinyl chloride, modified filler, aminopropylheptyl-cage polysilsesquioxane and ethylene-tetrafluoroethylene copolymer are introduced, and compounded with raw materials such as compatibilizer and heat stabilizer, so that the prepared chlorinated polyvinyl chloride composite material has good mechanical properties, corrosion resistance and high temperature resistance, and long service life. Among them, the chemical structure of the aminopropylheptyl-cage polysilsesquioxane contains a cage siloxane core, which is connected to the aminopropylheptyl, and the chlorinated polyvinyl chloride, maleic anhydride grafted chlorinated polyvinyl chloride, ethylene-tetrafluoroethylene copolymer, modified filler and heat stabilizer The raw materials synergistically act to help improve the high temperature resistance, mechanical properties and corrosion resistance of the chlorinated polyvinyl chloride composite material, improve impact strength, and extend service life.
[0007] Furthermore, the compatibilizer is at least one of methyl methacrylate-butadiene-styrene copolymer and styrene-acrylonitrile-glycidyl methacrylate copolymer.
[0008] Furthermore, the lubricant is at least one of calcium stearate, zinc stearate, polyethylene wax and oxidized polyethylene wax.
[0009] Furthermore, the heat stabilizer is at least one of dibutyltin dilaurate, dioctyltin laurate, 3-cyclohexylpropionic acid and zinc carbonate.
[0010] Furthermore, the heat stabilizer is composed of dioctyltin laurate, 3-cyclohexylpropionic acid and zinc carbonate in a weight ratio of 2-3:1-2:1-2. The use of the heat stabilizer is helpful to improve the high temperature resistance of the chlorinated polyvinyl chloride composite material.
[0011] Furthermore, the processing aid is an acrylic copolymer.
[0012] Furthermore, the preparation method of the modified filler comprises the following steps: A1. Add 60-70 parts of solvent, 10-14 parts of γ-aminopropyltriethoxysilane and 5-8 parts of polydimethylsiloxane by weight into a reaction vessel, stir and heat to 95-105° C. under a nitrogen atmosphere; A2, 10-14 parts of octadecyl methacrylate, 5-8 parts of hydroxyethyl acrylate, 5-8 parts of methyl methacrylate and 0.5-2g of initiator are mixed evenly, and then added dropwise to the reaction container at a uniform speed, the dropping time is 90-150min, and reacted at 95-105°C for 2-4h until the acrylic acid monomer is completely converted to obtain a light milky white transparent viscous liquid to obtain a modified resin; A3, after the nano inorganic filler and ethyl acetate are mixed evenly, a modified resin is added and mixed evenly, and then dried to obtain a modified filler; the weight ratio of the nano inorganic filler, ethyl acetate and modified resin is 10-15:8-12:1-2.
[0013] In the present invention, the modified filler is a silicone-acrylic resin modified filler. The present invention prepares the modified resin by adopting the above method, and the prepared modified resin is a modified silicone-acrylic resin, and then the modified resin is used to modify the nano inorganic filler. The nano inorganic filler is evenly dispersed in the composite material system, has good compatibility with various raw materials in the composite material, and can effectively improve the high temperature resistance, corrosion resistance and mechanical properties of the composite material.
[0014] Furthermore, in step A1, the solvent is at least one of ethyl acetate, butyl acetate and petroleum ether.
[0015] Furthermore, in step A2, the initiator is benzoyl peroxide and azobisisobutyronitrile.
[0016] Furthermore, in step A3, the nano inorganic filler is at least one of nano calcium carbonate, nano magnesium hydroxide and nano white carbon black, and the particle size of the nano inorganic filler is 50-100 nm.
[0017] Furthermore, the nano inorganic filler is composed of nano calcium carbonate, nano magnesium hydroxide and nano white carbon in a weight ratio of 5-10:5-10:4-8. By using the above nano inorganic filler and modifying it with a modified resin, it is evenly dispersed in the composite material system, effectively improving the mechanical properties and high temperature resistance of the composite material.
[0018] Furthermore, in step A3, the nano inorganic filler, ethyl acetate and modified resin are placed in a disperser for stirring and dispersing, the speed of the disperser is 3000-4000 rpmn, the stirring time is 30-60 min, and the drying temperature is 40-45°C.
[0019] Furthermore, the preparation method of maleic anhydride grafted chlorinated polyvinyl chloride comprises the following steps: B1, take 40-50 parts of chlorinated polyvinyl chloride and a swelling agent and mix them evenly, then add 4-6 parts of maleic anhydride and 1-2 parts of an initiator, and perform ultrasonic vibration at a temperature of 75-85° C. for 90-150 minutes; the mixing ratio of the chlorinated polyvinyl chloride and the solvent is 0.3-0.6 g / mL; B2. The product obtained in step B1 is vacuum filtered and then rinsed with water, filtered again, and then placed in a vacuum drying oven for vacuum drying at a drying temperature of 76-84° C. to obtain maleic anhydride grafted chlorinated polyvinyl chloride.
[0020] In the present invention, maleic anhydride grafted chlorinated polyvinyl chloride is prepared by adopting the above method. During the reaction process, the initiator decomposes under the temperature conditions set by the initiator to generate primary free radicals. Under the auxiliary action of ultrasound, the hydrogen on the main chain of the chlorinated polyvinyl chloride is taken away so that the chlorinated polyvinyl chloride forms a macromolecular free radical, which then reacts with maleic anhydride to prepare maleic anhydride grafted chlorinated polyvinyl chloride. The present invention grafts chlorinated polyvinyl chloride by adopting the above method, which helps to improve the thermal stability and processing performance of chlorinated polyvinyl chloride and improve its mechanical properties. In combination with other raw materials, the chlorinated polyvinyl chloride composite material can be endowed with good mechanical properties and high temperature resistance.
[0021] Furthermore, in step B1, maleic anhydride and the initiator are both dissolved in water in advance, and the concentration of the maleic anhydride aqueous solution is 4-6wt%; the concentration of the initiator aqueous solution is 1-2wt%.
[0022] Furthermore, in step B1, the swelling agent is at least one of acetone and cyclohexanone; and the initiator is at least one of ammonium persulfate and potassium sulfate. The swelling agent has a better swelling effect on chlorinated polyvinyl chloride, increases the specific surface area of chlorinated polyvinyl chloride, provides more reaction sites for it in the grafting reaction, and promotes the increase of the grafting rate.
[0023] The purpose of the present invention is achieved by the following technical solution: A method for preparing a chlorinated polyvinyl chloride composite material for a vehicle lamp cover comprises the following steps: (1) uniformly mixing the raw materials constituting the chlorinated polyvinyl chloride composite material according to a certain proportion to obtain a mixed material; (2) The mixed material obtained in step (1) is fed into an extruder for melt extrusion, and the extruded strips are cooled, dried, and then pelletized to obtain a chlorinated polyvinyl chloride composite material for a vehicle lamp cover.
[0024] In the step (2), a twin-screw extruder is used for melt extrusion, and the temperatures of the zones of the twin-screw extruder are: zone 1 temperature: 140-160°C, zone 2 temperature: 150-170°C, zone 3 temperature: 160-180°C, zone 4 temperature: 170-190°C, zone 5 temperature: 200-220°C, zone 6 temperature: 170-190°C, and the screw speed of the screw extruder is 400-500 rpm.
[0025] The beneficial effects of the present invention are as follows: the chlorinated polyvinyl chloride composite material for vehicle lampshades of the present invention uses chlorinated polyvinyl chloride as the main raw material, and introduces maleic anhydride grafted chlorinated polyvinyl chloride, modified filler, aminopropylheptyl-cage polysilsesquioxane and ethylene-tetrafluoroethylene copolymer, and each raw material is well matched, and the prepared chlorinated polyvinyl chloride composite material has good mechanical properties, corrosion resistance and high temperature resistance, and has a long service life. The preparation method of the chlorinated polyvinyl chloride composite material for vehicle lampshades is convenient to operate and control, has high production efficiency, is suitable for industrial production, and the prepared product has stable quality and reliable performance. DETAILED DESCRIPTION
[0026] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.
[0027] In some embodiments of the present invention, a chlorinated polyvinyl chloride composite material for a vehicle lampshade comprises the following raw materials in parts by weight: 70-80 parts of chlorinated polyvinyl chloride, 10-15 parts of maleic anhydride grafted chlorinated polyvinyl chloride, 8-14 parts of modified filler, 4-8 parts of compatibilizer, 4-8 parts of thermal stabilizer, 4-9 parts of ethylene-tetrafluoroethylene copolymer, 2-5 parts of lubricant, 2-5 parts of aminopropylheptyl-cage polysilsesquioxane, and 2-6 parts of processing aid. The chlorine content of the chlorinated polyvinyl chloride is 64-75%. A colorant may be added to the chlorinated polyvinyl chloride composite material as needed.
[0028] In some embodiments of the present invention, the compatibilizer is at least one of methyl methacrylate-butadiene-styrene copolymer and styrene-acrylonitrile-glycidyl methacrylate copolymer.
[0029] In some embodiments of the present invention, the lubricant is at least one of calcium stearate, zinc stearate, polyethylene wax and oxidized polyethylene wax.
[0030] In some embodiments of the present invention, the heat stabilizer is at least one of dibutyltin dilaurate, dioctyltin laurate, 3-cyclohexylpropionic acid and zinc carbonate.
[0031] In some embodiments of the present invention, the heat stabilizer is composed of dioctyltin laurate, 3-cyclohexylpropionic acid and zinc carbonate in a weight ratio of 2-3:1-2:1-2.
[0032] In some embodiments of the present invention, the heat stabilizer is composed of dioctyltin laurate, 3-cyclohexylpropionic acid and zinc carbonate in a weight ratio of 2-3:1-2:1-2.
[0033] In some embodiments of the present invention, the processing aid is an acrylic acid ester copolymer, and the acrylic acid ester copolymer is a styrene-methyl methacrylate copolymer.
[0034] In some embodiments of the present invention, the method for preparing the modified filler comprises the following steps: A1. Add 60-70 parts of solvent, 10-14 parts of γ-aminopropyltriethoxysilane and 5-8 parts of polydimethylsiloxane by weight into a reaction vessel, stir and heat to 95-105° C. under a nitrogen atmosphere; A2, 10-14 parts of octadecyl methacrylate, 5-8 parts of hydroxyethyl acrylate, 5-8 parts of methyl methacrylate and 0.5-2g of initiator are uniformly mixed, and then uniformly added dropwise to the reaction container for 90-150min, and reacted under azeotropic distillation conditions at 95-105°C for 2-4h until the acrylic acid monomer is completely converted to obtain a light milky white transparent viscous liquid to obtain a modified resin; A3, after the nano inorganic filler and ethyl acetate are mixed evenly, a modified resin is added and mixed evenly, and then dried to obtain a modified filler; the weight ratio of the nano inorganic filler, ethyl acetate and modified resin is 10-15:8-12:1-2.
[0035] In some embodiments of the present invention, in step A1, the solvent is at least one of ethyl acetate, butyl acetate and petroleum ether.
[0036] In some embodiments of the present invention, in step A2, the initiator is benzoyl peroxide and azobisisobutyronitrile.
[0037] In some embodiments of the present invention, in step A3, the nano inorganic filler is at least one of nano calcium carbonate, nano magnesium hydroxide and nano white carbon black, and the particle size of the nano inorganic filler is 50-100 nm.
[0038] In some embodiments of the present invention, the nano inorganic filler is composed of nano calcium carbonate, nano magnesium hydroxide and nano white carbon black in a weight ratio of 5-10:5-10:4-8.
[0039] In some embodiments of the present invention, in step A3, the nano inorganic filler, ethyl acetate and modified resin are placed in a disperser for stirring and dispersing, the speed of the disperser is 3000-4000 rpmn, the stirring time is 30-60 min; and the drying temperature is 40-45°C.
[0040] In some embodiments of the present invention, the method for preparing maleic anhydride grafted chlorinated polyvinyl chloride comprises the following steps: B1, take 40-50 parts of chlorinated polyvinyl chloride and a swelling agent and mix them evenly, then add 4-6 parts of maleic anhydride and 1-2 parts of an initiator, and perform ultrasonic vibration at a temperature of 75-85° C. for 90-150 minutes; the mixing ratio of the chlorinated polyvinyl chloride and the solvent is 0.3-0.6 g / mL; B2. The product obtained in step B1 is vacuum filtered and then rinsed with water, filtered again, and then placed in a vacuum drying oven for vacuum drying at a drying temperature of 76-84° C. to obtain maleic anhydride grafted chlorinated polyvinyl chloride.
[0041] In some embodiments of the present invention, in step B1, maleic anhydride and the initiator are both dissolved in water in advance, and the concentration of the maleic anhydride aqueous solution is 4-6wt%; the concentration of the initiator aqueous solution is 1-2wt%.
[0042] In some embodiments of the present invention, in step B1, the swelling agent is at least one of acetone and cyclohexanone; the initiator is at least one of ammonium persulfate and potassium sulfate. The swelling agent has a better swelling effect on chlorinated polyvinyl chloride, increases the specific surface area of chlorinated polyvinyl chloride, provides more reaction sites for it in the grafting reaction, and promotes the increase of grafting rate.
[0043] In some embodiments of the present invention, a method for preparing a chlorinated polyvinyl chloride composite material for a vehicle lamp cover comprises the following steps: (1) uniformly mixing the raw materials constituting the chlorinated polyvinyl chloride composite material according to a certain proportion to obtain a mixed material; (2) The mixed material obtained in step (1) is fed into an extruder for melt extrusion, and the extruded strips are cooled, dried, and then pelletized to obtain a chlorinated polyvinyl chloride composite material for a vehicle lamp cover.
[0044] In the step (2), a twin-screw extruder is used for melt extrusion, and the temperatures of the zones of the twin-screw extruder are: zone 1 temperature: 140-160°C, zone 2 temperature: 150-170°C, zone 3 temperature: 160-180°C, zone 4 temperature: 170-190°C, zone 5 temperature: 200-220°C, zone 6 temperature: 170-190°C, and the screw speed of the screw extruder is 400-500 rpm.
[0045] Example 1 This embodiment provides a chlorinated polyvinyl chloride composite material for a car lampshade, comprising the following raw materials in parts by weight: 75 parts of chlorinated polyvinyl chloride, 12 parts of maleic anhydride grafted chlorinated polyvinyl chloride, 10 parts of modified filler, 6 parts of compatibilizer, 5 parts of thermal stabilizer, 7 parts of ethylene-tetrafluoroethylene copolymer, 3 parts of lubricant, 3 parts of aminopropylheptyl-cage polysilsesquioxane, and 4 parts of processing aid. The chlorinated polyvinyl chloride uses PolyOne chlorinated polyvinyl chloride EC900 and Arkema CPVC783, and the weight ratio between the two is 3:2. The ethylene-tetrafluoroethylene copolymer uses Daikin Neoflon ETFE EP-541.
[0046] Furthermore, the compatibilizer is methyl methacrylate-butadiene-styrene copolymer. In this embodiment, electrochemical TH-21B methyl methacrylate-butadiene-styrene copolymer is used. The lubricant is composed of calcium stearate and polyethylene wax in a weight ratio of 1:1.
[0047] Furthermore, the heat stabilizer is composed of dioctyltin laurate, 3-cyclohexylpropionic acid and zinc carbonate in a weight ratio of 2.5:2:1.
[0048] Furthermore, the processing aid is an acrylic copolymer, and the acrylic copolymer is MS Chimei PM-600 styrene-methyl methacrylate copolymer.
[0049] Furthermore, the preparation method of the modified filler comprises the following steps: A1. Add 65 parts of solvent, 12 parts of γ-aminopropyltriethoxysilane and 6 parts of polydimethylsiloxane by weight into a reaction vessel, stir and heat to 100° C. under a nitrogen atmosphere; A2, 12 parts of octadecyl methacrylate, 7 parts of hydroxyethyl acrylate, 6 parts of methyl methacrylate and 1 g of initiator were uniformly mixed, and then uniformly added dropwise to the reaction container for 120 min, and reacted for 3 h under azeotropic distillation conditions at 100 ° C until the acrylic acid monomer was completely converted to obtain a light milky white transparent viscous liquid to obtain a modified resin; A3, after the nano inorganic filler and ethyl acetate are mixed evenly, a modified resin is added and mixed evenly, and then dried to obtain a modified filler; the weight ratio of the nano inorganic filler, ethyl acetate and modified resin is 12:10:1.5.
[0050] Furthermore, in step A1, the solvent is composed of ethyl acetate and butyl acetate in a weight ratio of 2:1.
[0051] Furthermore, in step A2, the initiator is benzoyl peroxide.
[0052] Furthermore, the nano inorganic filler is composed of nano calcium carbonate, nano magnesium hydroxide and nano white carbon in a weight ratio of 6:6:5. The particle size of the nano inorganic filler is 50-100 nm.
[0053] Furthermore, in step A3, the nano inorganic filler, ethyl acetate and modified resin are placed in a disperser for stirring and dispersing, the speed of the disperser is 3500 rpmn, the stirring time is 45 min, and the drying temperature is 42°C.
[0054] Furthermore, the preparation method of maleic anhydride grafted chlorinated polyvinyl chloride comprises the following steps: B1, take 45 parts of chlorinated polyvinyl chloride and a swelling agent and mix them evenly, then add 5 parts of maleic anhydride and 1.5 parts of an initiator, and perform ultrasonic vibration at 80°C for 120 minutes; the mixing ratio of the chlorinated polyvinyl chloride and the solvent is 0.5 g / mL; the chlorinated polyvinyl chloride adopts PolyOne chlorinated polyvinyl chloride EC900; B2. The product obtained in step B1 is vacuum filtered and then rinsed with water, filtered again, and then placed in a vacuum drying oven for vacuum drying at a drying temperature of 80° C. to obtain maleic anhydride grafted chlorinated polyvinyl chloride.
[0055] Furthermore, in step B1, maleic anhydride and the initiator are both dissolved in water in advance, and the concentration of the maleic anhydride aqueous solution is 5 wt %; the concentration of the initiator aqueous solution is 1.5 wt %.
[0056] Furthermore, in step B1, the swelling agent is acetone, and the initiator is potassium persulfate.
[0057] In this embodiment, a method for preparing a chlorinated polyvinyl chloride composite material for a vehicle lamp cover comprises the following steps: (1) uniformly mixing the raw materials constituting the chlorinated polyvinyl chloride composite material according to a certain proportion to obtain a mixed material; (2) The mixed material obtained in step (1) is fed into an extruder for melt extrusion, and the extruded strips are cooled, dried, and then pelletized to obtain a chlorinated polyvinyl chloride composite material for a vehicle lamp cover.
[0058] In the step (2), a twin-screw extruder is used for melt extrusion, and the temperatures of the zones of the twin-screw extruder are: zone 1 temperature: 140°C, zone 2 temperature: 160°C, zone 3 temperature: 170°C, zone 4 temperature: 180°C, zone 5 temperature: 200°C, zone 6 temperature: 180°C, and the screw speed of the screw extruder is 500 rpm.
[0059] Example 2 The present embodiment provides a chlorinated polyvinyl chloride composite material for a vehicle lamp cover, comprising the following raw materials in parts by weight: 75 parts of chlorinated polyvinyl chloride, 11 parts of maleic anhydride grafted chlorinated polyvinyl chloride, 8 parts of a modified filler, 5 parts of a compatibilizer, 4 parts of a heat stabilizer, 5 parts of an ethylene-tetrafluoroethylene copolymer, 2 parts of a lubricant, 3 parts of aminopropylheptyl-cage polysilsesquioxane, and 2 parts of a processing aid.
[0060] Furthermore, the compatibilizer is methyl methacrylate-butadiene-styrene copolymer.
[0061] Furthermore, the preparation method of the modified filler comprises the following steps: A1. Add 60 parts of solvent, 10 parts of γ-aminopropyltriethoxysilane and 5 parts of polydimethylsiloxane by weight into a reaction vessel, stir and heat to 95° C. under a nitrogen atmosphere; A2, 10 parts of octadecyl methacrylate, 5 parts of hydroxyethyl acrylate, 6 parts of methyl methacrylate and 0.8 g of initiator were mixed evenly, and then added dropwise to the reaction container at a uniform speed for 110 min, and reacted for 3 h under azeotropic distillation conditions at 100 ° C until the acrylic acid monomer was completely converted to obtain a light milky white transparent viscous liquid to obtain a modified resin; A3. After uniformly mixing the nano inorganic filler and ethyl acetate, add the modified resin and mix them uniformly, then dry them to obtain a modified filler; the weight ratio of the nano inorganic filler, ethyl acetate and modified resin is 10:8:1.5.
[0062] Furthermore, the nano inorganic filler is composed of nano calcium carbonate, nano magnesium hydroxide and nano white carbon black in a weight ratio of 5:5:4.
[0063] Furthermore, in step A3, the nano inorganic filler, ethyl acetate and modified resin are placed in a disperser for stirring and dispersing, the speed of the disperser is 4000 rpmn, the stirring time is 60 min, and the drying temperature is 40°C.
[0064] Furthermore, the preparation method of maleic anhydride grafted chlorinated polyvinyl chloride comprises the following steps: B1, take 40 parts of chlorinated polyvinyl chloride and a swelling agent and mix them evenly, then add 4 parts of maleic anhydride and 1.2 parts of an initiator, and perform ultrasonic vibration at 80°C for 120 minutes; the mixing ratio of the chlorinated polyvinyl chloride and the solvent is 0.5 g / mL; B2. The product obtained in step B1 is vacuum filtered and then rinsed with water, filtered again, and then placed in a vacuum drying oven for vacuum drying at a drying temperature of 80° C. to obtain maleic anhydride grafted chlorinated polyvinyl chloride.
[0065] In this embodiment, a method for preparing a chlorinated polyvinyl chloride composite material for a vehicle lamp cover comprises the following steps: (1) uniformly mixing the raw materials constituting the chlorinated polyvinyl chloride composite material according to a certain proportion to obtain a mixed material; (2) The mixed material obtained in step (1) is fed into an extruder for melt extrusion, and the extruded strips are cooled, dried, and then pelletized to obtain a chlorinated polyvinyl chloride composite material for a vehicle lamp cover.
[0066] In the step (2), a twin-screw extruder is used for melt extrusion, and the temperatures of the zones of the twin-screw extruder are: zone 1 temperature: 145°C, zone 2 temperature: 160°C, zone 3 temperature: 165°C, zone 4 temperature: 185°C, zone 5 temperature: 215°C, zone 6 temperature: 185°C, and the screw speed of the screw extruder is 400 rpm.
[0067] The rest of the contents of this comparative example are the same as those of Example 1 and will not be described again here.
[0068] Example 3 The present embodiment provides a chlorinated polyvinyl chloride composite material for a vehicle lamp cover, comprising the following raw materials in parts by weight: 79 parts of chlorinated polyvinyl chloride, 14 parts of maleic anhydride grafted chlorinated polyvinyl chloride, 14 parts of a modified filler, 7 parts of a compatibilizer, 6 parts of a heat stabilizer, 6 parts of an ethylene-tetrafluoroethylene copolymer, 4 parts of a lubricant, 4 parts of aminopropylheptyl-cage polysilsesquioxane, and 5 parts of a processing aid.
[0069] Furthermore, the lubricant is composed of zinc stearate and polyethylene wax in a weight ratio of 2:1.
[0070] Furthermore, the heat stabilizer is composed of dioctyltin laurate, 3-cyclohexylpropionic acid and zinc carbonate in a weight ratio of 3:2:1.
[0071] Furthermore, the preparation method of the modified filler comprises the following steps: A1. Add 65 parts of solvent, 12 parts of γ-aminopropyltriethoxysilane and 8 parts of polydimethylsiloxane by weight into a reaction vessel, stir and heat to 100° C. under a nitrogen atmosphere; A2, 13 parts of octadecyl methacrylate, 7 parts of hydroxyethyl acrylate, 7 parts of methyl methacrylate and 1.8 g of initiator were mixed evenly, and then added dropwise to the reaction container at a uniform speed for 120 min, and reacted for 3.5 h under azeotropic distillation conditions at 105 ° C until the acrylic acid monomer was completely converted to obtain a light milky white transparent viscous liquid to obtain a modified resin; A3. After uniformly mixing the nano inorganic filler and ethyl acetate, add the modified resin and mix them uniformly, then dry them to obtain a modified filler; the weight ratio of the nano inorganic filler, ethyl acetate and modified resin is 15:12:2.
[0072] Furthermore, the nano inorganic filler is composed of nano calcium carbonate, nano magnesium hydroxide and nano white carbon black in a weight ratio of 1:1:1.
[0073] Furthermore, the preparation method of maleic anhydride grafted chlorinated polyvinyl chloride comprises the following steps: B1. Take 45 parts of chlorinated polyvinyl chloride and a swelling agent and mix them evenly, then add 5.5 parts of maleic anhydride and 1.2 parts of an initiator, and perform ultrasonic vibration at 80° C. for 120 minutes; the mixing ratio of the chlorinated polyvinyl chloride and the solvent is 0.5 g / mL; B2. The product obtained in step B1 is vacuum filtered and then rinsed with water, filtered again, and then placed in a vacuum drying oven for vacuum drying at a drying temperature of 78° C. to obtain maleic anhydride grafted chlorinated polyvinyl chloride.
[0074] Furthermore, in step B1, maleic anhydride and the initiator are both dissolved in water in advance, and the concentration of the maleic anhydride aqueous solution is 5 wt %; the concentration of the initiator aqueous solution is 1.5 wt %.
[0075] Furthermore, in step B1, the swelling agent is acetone; and the initiator is potassium persulfate.
[0076] The rest of the contents of this comparative example are the same as those of Example 1 and will not be described again here.
[0077] Example 4 The present embodiment provides a chlorinated polyvinyl chloride composite material for a vehicle lamp cover, comprising the following raw materials in parts by weight: 79 parts of chlorinated polyvinyl chloride, 12 parts of maleic anhydride grafted chlorinated polyvinyl chloride, 10 parts of a modified filler, 6 parts of a compatibilizer, 5 parts of a heat stabilizer, 4 parts of an ethylene-tetrafluoroethylene copolymer, 3 parts of a lubricant, 2 parts of aminopropylheptyl-cage polysilsesquioxane, and 4 parts of a processing aid.
[0078] Furthermore, the preparation method of the modified filler comprises the following steps: A1. Add 65 parts of solvent, 12 parts of γ-aminopropyltriethoxysilane and 6 parts of polydimethylsiloxane by weight into a reaction vessel, stir and heat to 100° C. under a nitrogen atmosphere; A2, 12 parts of octadecyl methacrylate, 7 parts of hydroxyethyl acrylate, 6 parts of methyl methacrylate and 1 g of initiator were uniformly mixed, and then uniformly added dropwise to the reaction container for 120 min, and reacted for 3 h under azeotropic distillation conditions at 100 ° C until the acrylic acid monomer was completely converted to obtain a light milky white transparent viscous liquid to obtain a modified resin; A3, after the nano inorganic filler and ethyl acetate are mixed evenly, a modified resin is added and mixed evenly, and then dried to obtain a modified filler; the weight ratio of the nano inorganic filler, ethyl acetate and modified resin is 12:10:1.5.
[0079] Furthermore, in step A1, the solvent is composed of ethyl acetate and butyl acetate in a weight ratio of 2:1.
[0080] Furthermore, in step A2, the initiator is benzoyl peroxide.
[0081] Furthermore, the nano inorganic filler is composed of nano calcium carbonate, nano magnesium hydroxide and nano white carbon black in a weight ratio of 6:6:5.
[0082] Furthermore, in step A3, the nano inorganic filler, ethyl acetate and modified resin are placed in a disperser for stirring and dispersing, the speed of the disperser is 3500 rpmn, the stirring time is 45 min, and the drying temperature is 42°C.
[0083] Furthermore, the preparation method of maleic anhydride grafted chlorinated polyvinyl chloride comprises the following steps: B1, take 45 parts of chlorinated polyvinyl chloride and a swelling agent and mix them evenly, then add 5 parts of maleic anhydride and 1.5 parts of an initiator, and perform ultrasonic vibration at 80°C for 120 minutes; the mixing ratio of the chlorinated polyvinyl chloride and the solvent is 0.5 g / mL; B2. The product obtained in step B1 is vacuum filtered and then rinsed with water, filtered again, and then placed in a vacuum drying oven for vacuum drying at a drying temperature of 80° C. to obtain maleic anhydride grafted chlorinated polyvinyl chloride.
[0084] The rest of the contents of this comparative example are the same as those of Example 1 and will not be described again here.
[0085] Comparative Example 1 The difference between this comparative example and Example 1 is that the chlorinated polyvinyl chloride composite material provided in this comparative example does not contain maleic anhydride grafted chlorinated polyvinyl chloride and ethylene-tetrafluoroethylene copolymer, and an equal amount of chlorinated polyvinyl chloride is used instead.
[0086] Comparative Example 2 The difference between this comparative example and Example 1 is that the chlorinated polyvinyl chloride composite material provided in this comparative example uses an equal amount of nano inorganic filler to replace the modified filler in Example 1, and the nano inorganic filler is not modified by a modified resin.
[0087] Comparative Example 3 The difference between this comparative example and Example 1 is that the chlorinated polyvinyl chloride composite material provided in this comparative example does not contain aminopropylheptyl-cage polysilsesquioxane, and an equal amount of processing aid is used instead.
[0088] The present invention uses the chlorinated polyvinyl chloride composite materials for vehicle lamp covers prepared in the above-mentioned Examples 1-3 and Comparative Examples 1-2 to form strips through an injection molding machine for performance testing. The test results are shown in the following table: project Izod beam notched impact strength / KJ / m2 Bending strength / Mpa Tensile strength / Mpa Vicat softening temperature / ℃ Example 1 27.9 114 55.2 115.5 Example 2 26.4 109 59.3 116.7 Example 3 27.1 116 58.4 144.7 Example 4 27.4 111 56.3 115.0 Comparative Example 1 20.9 101 62.1 107.2 Comparative Example 2 22.1 103 61.5 115.8 Comparative Example 3 23.6 106 59.4 108.9 Among them, the cantilever beam notched impact strength is tested according to GB / T 1843-2008, the test temperature at room temperature is 23°C, and the standard sample size is 80mm*10mm*4mm. The tensile strength is tested according to GB / T1040.1-2006, and the test rate is 50mm / min. The bending strength is tested according to GB / T 9341-2000. The Vicat softening temperature is tested according to GB / T1633-2000. The UL-94 flame retardant grade of the embodiments 1-4 is V-0, showing good flame retardancy. The chlorinated polyvinyl chloride composite material of embodiments 1-4 is made into a sample with a thickness of 0.8mm. The surface of the sample is flat, without water marks and foreign matter. The transmittance is tested according to GB / T2410-2008, and the transmittance of the chlorinated polyvinyl chloride composite material of embodiments 1-4 is measured to be above 80%. The thermal stability time was measured according to GB / T 2917.1-2002. The thermal stability time / min at 200°C of the chlorinated polyvinyl chloride composite materials in Examples 1-4 was 75.1 min, 73.4 min, 72.2 min and 75.6 min, respectively, showing good thermal stability.
[0089] According to GB11547-2008, the chlorinated polyvinyl chloride composite material specimens of Examples 1-4 and Comparative Examples 1-3 were immersed in 36% concentrated hydrochloric acid solution and 40% sodium hydroxide solution respectively, and the immersion conditions were 23°C*168hr. The changes in their appearance were observed after immersion. It can be found that the appearance of the specimens of Examples 1-4 and Comparative Examples 1-3 did not change, the surface was not sticky, there were no bubbles, small pits, silver streaks, cracks and warping, and they had good corrosion resistance.
[0090] In summary, the chlorinated polyvinyl chloride composite material prepared by the present invention has good overall mechanical properties, excellent impact resistance, corrosion resistance and high temperature resistance, and long service life. The preparation method of the chlorinated polyvinyl chloride composite material for vehicle lamp cover has simple process, convenient operation and control, high production efficiency, is suitable for industrial production, and the prepared product has stable quality and reliable performance.
[0091] The above specific embodiments are further explanations of the technical solutions and beneficial effects of the present invention, and are not limitations of the implementation methods. For those skilled in the art, any obvious replacements that do not depart from the concept of the present invention are within the protection scope of the present invention.
Claims
1. A chlorinated polyvinyl chloride composite material for a vehicle lamp cover, characterized in that: The invention comprises the following raw materials in parts by weight: 70-80 parts of chlorinated polyvinyl chloride, 10-15 parts of maleic anhydride grafted chlorinated polyvinyl chloride, 8-14 parts of modified filler, 4-8 parts of compatibilizer, 4-8 parts of heat stabilizer, 4-9 parts of ethylene-tetrafluoroethylene copolymer, 2-5 parts of lubricant, 2-5 parts of aminopropylheptyl-cage polysilsesquioxane and 2-6 parts of processing aid.
2. The chlorinated polyvinyl chloride composite material for vehicle lamp cover according to claim 1, characterized in that: The compatibilizer is at least one of styrene-acrylonitrile-glycidyl methacrylate copolymer and methyl methacrylate-butadiene-styrene copolymer.
3. The chlorinated polyvinyl chloride composite material for vehicle lamp cover according to claim 1, characterized in that: The lubricant is at least one of calcium stearate, zinc stearate, polyethylene wax and oxidized polyethylene wax.
4. The chlorinated polyvinyl chloride composite material for vehicle lamp cover according to claim 1, characterized in that: The heat stabilizer is at least one of dibutyltin dilaurate, dioctyltin laurate, 3-cyclohexylpropionic acid and zinc carbonate.
5. The chlorinated polyvinyl chloride composite material for vehicle lamp cover according to claim 1, characterized in that: The processing aid is an acrylic acid ester copolymer.
6. The chlorinated polyvinyl chloride composite material for vehicle lamp cover according to claim 1, characterized in that: The preparation method of the modified filler comprises the following steps: A1. Add 60-70 parts of solvent, 10-14 parts of γ-aminopropyltriethoxysilane and 5-8 parts of polydimethylsiloxane by weight into a reaction vessel, stir and heat to 95-105° C. under a nitrogen atmosphere; A2, 10-14 parts of octadecyl methacrylate, 5-8 parts of hydroxyethyl acrylate, 5-8 parts of methyl methacrylate and 0.5-2g of initiator are uniformly mixed, and then dropwise added into the reaction container at a uniform speed, the dropping time is 90-150min, and reacted at 95-105°C for 2-4h until the acrylic acid monomer is completely converted to obtain a modified resin; A3, after the nano inorganic filler and ethyl acetate are mixed evenly, a modified resin is added and mixed evenly, and then dried to obtain a modified filler; the weight ratio of the nano inorganic filler, ethyl acetate and modified resin is 10-15:8-12:1-2.
7. The chlorinated polyvinyl chloride composite material for vehicle lamp cover according to claim 6, characterized in that: In the step A1, the solvent is at least one of ethyl acetate, butyl acetate and petroleum ether.
8. The chlorinated polyvinyl chloride composite material for vehicle lamp cover according to claim 6, characterized in that: In the step A3, the nano inorganic filler is at least one of nano calcium carbonate, nano magnesium hydroxide and nano white carbon black.
9. The method for preparing the chlorinated polyvinyl chloride composite material for vehicle lamp cover according to any one of claims 1 to 8, characterized in that: The steps include: (1) uniformly mixing the raw materials constituting the chlorinated polyvinyl chloride composite material according to a certain proportion to obtain a mixed material; (2) The mixed material obtained in step (1) is fed into an extruder for melt extrusion, and the extruded strips are cooled, dried, and then pelletized to obtain a chlorinated polyvinyl chloride composite material for a vehicle lamp cover.
10. The method for preparing the chlorinated polyvinyl chloride composite material for vehicle lamp cover according to claim 9, characterized in that: In the step (2), a twin-screw extruder is used for melt extrusion, and the temperatures of the zones of the twin-screw extruder are: zone 1 temperature: 140-160°C, zone 2 temperature: 150-170°C, zone 3 temperature: 160-180°C, zone 4 temperature: 170-190°C, zone 5 temperature: 200-220°C, zone 6 temperature: 170-190°C, and the screw speed of the screw extruder is 400-500 rpm.
Citation Information
Patent Citations
Preparation method of maleic anhydride grafted chlorinated polyvinyl chloride composite material
CN103073830A
Chlorinated polyvinyl chloride modified material and preparation method thereof
CN103102632A
Chlorinated polyvinyl chloride pipe for automatically spraying water to extinguish fire and preparation method thereof
CN115449169A
Chlorinated polyvinyl chloride resin composition, extruded sheet and method for manufacturing the same
US20240117176A1
Cited By
Flame-retardant impact-resistant CPVC (chlorinated polyvinyl chloride) electric tube material and preparation method thereof
CN122325906A